Alteration in electrocatalytic water splitting activity of reduced graphene oxide through simultaneous and individual doping of Lewis acid/base center. (1st December 2020) - Shit, Subhasis; Samanta, Prakas; Bolar, Saikat; Murmu, Naresh Chandra; Kuila, Tapas
Highlights: Lewis base and acid center enhances the substrate adsorption efficiency of rGO. Simultaneous and individual B/N incorporation alters the HER and OER mechanistic. Substrate diffusion governs the HER process catalyzed by doped rGO. Charge transfer mechanistic governs the doped rGO catalyzed OER mechanistic. B, N co-doped rGO is superior electrocatalysts for HER and N-doped rGO for OER. Abstract: Substrate adsorption-desorption is an important aspect in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) catalysis process. The B and N are two neighboring elements of C which has Lewis acid and base characteristics. However, any thorough investigation has not been probed till date to understand the effect of simultaneous and individual incorporation of these Lewis acid and base centers in graphene towards electrocatalytic activity. In this investigation it was found that the incorporation of B and N in reduced graphene oxide (rGO) facilitated substrate adsorption-desorption and also modulated lattice parameters and electronic structure of it. Although N doped rGO showed better substrate adsorption efficiency in HER however, the substrate diffusion was sluggish in this case. Despite of moderate substrate adsorption efficiency of B and N-doped rGO, it showed better HER catalytic activity due to faster substrate diffusion and achieved 550 mA cm −2 current density at 327 mV overpotential. The B-doped rGO showed better substrate adsorption efficiency in OER. However, due to better charge transfer efficiency of N-doped rGO, it showed superior OER catalytic activity as OER was governed by charge transfer kinetics. In addition to electrocatalytic efficiency, the mechanistic of the electrocatalysis process also altered due to the simultaneous and individual incorporation of Lewis acid and base centers. Graphical abstract: Image, graphical abstract